Age-Related Impairment of Quality of Joint Motion in Vibroarthrographic Signal Analysis. (23rd February 2015) - Bączkowicz, Dawid; Majorczyk, Edyta; Kręcisz, Krzysztof
Abstract : Aging is associated with degenerative changes in articular surfaces leading to quantitative and qualitative impairment of joint motion. Therefore, the aim of this study is to evaluate an age-related quality of the patellofemoral joint (PFJ) motion in the vibroarthrographic (VAG) signal analysis. Two hundred and twenty individuals were enrolled in this study and divided into five groups according to age. The VAG signals were collected during flexion/extension knee motion using an acceleration sensor and described using four parameters (VMS, P1, P2, and H ). We observed that values of parameters VMS, P1, and P2 increase in accordance with the age, but H level decreases. The most significant differences were achieved between the youngest and the oldest participants' groups. Moreover, we show that parameters VMS, P1, and P2 positively correlate with age, contrary to negatively associated H parameter. Our results suggest that the impairment of joint motion is a result of age-related osteoarticular degenerative changes.